Type 2 Diabetes Prescribing Habits Amongst Providers to an Underserved Population - Cynthia King; Atem Fontem; Benjamin King; Dave Gothard (INNOVATIONS in Pharmacy, 2019)
Introduction: Type 2 diabetes mellitus (T2DM) affected over 30 million individuals in the United States as of 2015. Due to the national diabetes guidelines recommending drug selection based on several patient specific factors and varying formulary restrictions, prescribers are often inundated when selecting treatment. Currently, limited evidence is available regarding the primary factors influencing prescribers’ drug therapy selection.